PENGARUH PENERAPAN MODEL TAI SECARA DARING DENGAN VIDEO PEMBELAJARAN TERHADAP PEMAHAMAN KONSEP MATEMATIS PESERTA DIDIK KELAS VIII SMPN 1 HARAU - Elia Rahmi (Jurnal Edukasi dan Penelitian Matematika, 2020)
Understanding mathematical concept is one of expected of learning mathematics in junior high school. According to result of observations  in SMPN 1 Harau, understanding mathematical consept in class VIII is still can be improve. One of the causes of the low understanding mathematical concept by students is that the learning model applied does not actively involve students to build knowledge. Moreover, learning from home requires students to be active in developing concept independently existing learning resources. One of the models that can be applied is the type of cooperatife learning model type Team Assisted Individualization. Beside that, during learning with that model, videos are also used as learning material . Based on result and quizzed, it was concluded that understanding the mathematical concepts of students learning after applying cooperative learning model type Team Assisted Individualization is better than another students learing without that model in class VIII SMPN 1 Harau.Keywords—Understanding of Mathematical Concept, Team Assisted Individualization, Online Study, COVID-19